Predictors of seizure onset in Rett syndrome - Jian, Le; Nagarajan, L.; De Klerk, N.; Ravine, D.; Bower, C.; Anderson, A.; Williamson, S.; Christodoulou, J.; Leonard, H. (Mosby, Inc., 2006)
Rett syndrome (RTT) is a severe neurodevelopmental disorder mainly affecting female patients and caused by mutationsin the methyl-CpG binding protein 2 (MECP2) gene. Major features include loss of acquired skills, such as speech andpurposeful hand use, and the development of characteristic repetitive hand stereotypies, after relatively normal earlydevelopment. Other features include deceleration of head growth, impaired locomotion, autonomic dysfunction (manifestparticularly by respiratory abnormalities), scoliosis, and epilepsy. Epilepsy, which occurs in 50% to 94% of cases, and may be medically refractory, is among the most challenging of the comorbidities for those affected and their families. However, little is known about the predictors of seizures, including the relation, if any, to the underlying gene defect.This study explores possible genetic and other risk factors for seizure onset in RTT by using an Australian population-based longitudinal data set.